PENGARUH IKLAN BALIHO PIZZA HUT PALU TERHADAP MINAT BELI KONSUMEN DI KOTA PALU - Pradana, Rhizky Rizaldy (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2020)
The background of this research aims to determine the influence of Palu Pizza Hut billboard advertising on consumer buying interest in the city of Palu. The independent variables studied are typography (X1), illustrations (X2), color (X3), lines (X4), layout (X5) (which are derivative variables from elements of visual communication design) with the dependent variable namely consumer buying interest in the city of Palu. To find out how much influence the independent variables (typography, illustrations, colors, lines, layout) have on the dependent variable (consumer buying interest), multiple regression analysis was used with the F test analysis method. This research used a sample of 50 respondents from Palu Pizza Hut consumers. Meanwhile, sampling used random sampling analysis techniques. The tests used to test research instruments were validity tests, reliability tests and normality tests. Hypothesis testing uses the F test and, while to analyze the data, multiple regression analysis is used. The results of this research show that there is an influence between typography (X1), illustrations (X2), color (X3), lines (X4), layout (X5) on Pizza Hut Palu consumer buying interest (Y) with a contribution value of 41.6%, while the remaining 58.4% are other variables not examined in this study. This means that the hypothesis Ha is accepted and Ho is rejected. From this research, it was also concluded that the more dominant element in influencing the purchasing interest of Pizza Hut Palu consumers is layout (X5). Layout becomes the more dominant element.